Estruturas biogênicas em latossolos de chapadões, Uberlândia MG - Melo Júnior, Heliomar Baleeiro de (2012)
The biological activity in soil can interfere enough on its morphology, particularly in the structure as to be considered in the classification system developed soils (Soil Taxonomy). In tropical conditions the magnitude of the effects of biological activity in soil is even greater. However, morphological characteristics of biogenic nature has not been taken into consideration by the Brazilian System of Soil Classification (SiBCS). The effects of activity on the morphology pedofauna range from bioturbation, which may affect the development of pedogenetic structures, to produce structures that persist within the soil. Whereas the morphological description of soil characteristics should be recorded under the pedogenic processes, was developed for the purpose of this study provide a first approximation to the description of structure bioplasmadas of common occurrence in many Brazilian soils. For this purpose were examined soils, in areas of plateau due to the outstanding performance pedofauna pedoambientais due to the variations that occurred in these areas. Size classes are presented for different types of biogenic structures, such as a proposal that considers the relevance of biological activity to some extent already covered by the Soil Taxonomy, motivated by numerous field observations and several studies have developed related to the action in the pedofauna Brazilian soils. In the morphological characterization of some soils, the abundance and diversity, is essential to an appropriate mention biogenic structures, which is not traditionally done.